2006
DOI: 10.1111/j.1524-4725.2006.32100.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesotherapy and Phosphatidylcholine Injections: Historical Clarification and Review

Abstract: BACKGROUND Mesotherapy was originally conceived in Europe as a method of utilizing cutaneous injections containing a mixture of compounds for the treatment of local medical and cosmetic conditions. Although mesotherapy was traditionally employed for pain relief, its cosmetic applications, particularly fat and cellulite removal, have recently received attention in the United States. Another treatment for localized fat reduction, which was popularized in Brazil and uses injections of phosphatidylcholine, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
125
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 46 publications
0
125
0
10
Order By: Relevance
“…In 1937, Aron published a study about an intradermal injection of a histamine solution and concluded that intradermal injections of whatever product, when given into a painful location, would have an analgesic effect. 3 However, it was with Pistor that intradermotherapy received more attention, when he founded the French Society of Mesotherapy in 1964 and the technique became known throughout the world.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1937, Aron published a study about an intradermal injection of a histamine solution and concluded that intradermal injections of whatever product, when given into a painful location, would have an analgesic effect. 3 However, it was with Pistor that intradermotherapy received more attention, when he founded the French Society of Mesotherapy in 1964 and the technique became known throughout the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[47][48][49] Some studies have been revised regarding the role of mesotherapy in gynoid lipodystrophy 50 and others regarding the role of mesotherapy lipolysis. 3,6,51 These revisions offer the conclusion that, theoretically, a subcutaneous injection of specified products can function, but they lack indexed scientific publications on which to base this technique.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a clinically used PPC formulation consists of PPC and SD [6]. A PPC formulation has been used as a safe non-surgical method to melt fat deposits [7]. Previous clinical reports also have demonstrated that subcutaneous injection of a PPC formulation breaks up fat deposits [3, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…A PPC formulation has been used as a safe non-surgical method to melt fat deposits [7]. Previous clinical reports also have demonstrated that subcutaneous injection of a PPC formulation breaks up fat deposits [3, 7, 8]. However, since SD not only causes severe necrosis and inflammation in human lipomas [9], but also induces fat cell decomposition in a nonspecific manner due to its surfactant properties [10], a PPC formulation without SD is highly required.…”
Section: Introductionmentioning
confidence: 99%